Aplikasi Monitoring Data Imunisasi Berkala Untuk Meningkatkan Pelayanan Posyandu Menggunakan Metode RAD Berbasis Android - Lela Triana; Ria Andryani; Kurniawan Kurniawan (ISB Atma Luhur, 2021)
In an effort to reduce the mortality rate due to infection in infants, immunization activities are carried out. Implementation of immunization, namely through Integrated Service Posts. In the current system, child immunization data is recorded on the KMS (Kartu Menuju Sehat) that parents bring to the immunization program. The card is prone to missing, which causes parents to not have their child's immunization history data. The existence of a computerized application can help the health service process to be faster and provide valid and up to date data. Immunization data monitoring application is an application that was built to help organize the data into information needed to support routine monitoring activities at the public health center of Pembina. The design of this application uses the Unified Modeling Language (UML) and is developed using the Rapid Application Development (RAD) method that can produce systems quickly and directly involve the user in the application development process. This research resulted in an immunization data monitoring application intended for parents and officers of the Integrated Service Post at public health center.